Safety and efficacy of oil palm phenolic supplementation in improving lipid profile among hyperlipidemic adults: a phase 2, randomized, double-blind, placebo-controlled clinical trial - Muhammad Ismail Tadj, Nur Balqis; Ibrahim, Nurul `Izzah; Tg Abu Bakar Sidik, Tg Mohd Ikhwan; Zulfarina, Mohamed S.; Haji Mohd Saad, Qodriyah; Leow, Soon-Sen; Fairus, Syed; Naina Mohamed, Isa (Frontiers in Pharmacology, 2023)
Introduction: Oil palm phenolic (OPP) is an antioxidant aqueous palm oil by-product and contains a high amount of phenolics. OPP has been proven to have many therapeutical benefits, and one of them is as an antihyperlipidemic agent. The previous phase 1 clinical trial proved OPP was safe to be orally consumed by healthy volunteers and yielded a good lipid profile. Thus, this phase 2 clinical trial was conducted to determine the effectiveness of OPP in improving the lipid profile among hyperlipidemic subjects. Methods: A parallel, placebo-controlled, randomized, double-blinded clinical trial was conducted for 2 months on 50 hyperlipidemic subjects aged 20–50 years old. The subjects were randomly distributed to two treatment arms with 25 participants each: control/placebo (11 males and 14 females) and 250 mg of OPP (10 males and 15 females). The subjects were required to consume one capsule per day for 60 days. Fasting blood sampling for routine blood profile (hematology, liver function, renal function, and lipid) analysis and a medical examination were conducted at baseline, day 30, and day 60. t-test analysis was used to compare the difference between two test groups. Results: The baseline lipid profile between control group (TC, 5.78 ± 0.52 mmol/L; LDL, 3.88 ± 0.51 mmol/L; HDL, 1.30 ± 0.25; TG, 1.30 ± 0.82), and 250 mg OPP (TC, 5.76 ± 0.54 mmol/L; LDL, 3.82 ± 0.59 mmol/L; HDL, 1.37 ± 0.34; TG, 1.25 ± 0.54) is insignificant. No serious adverse events (SAEs) were reported. No abnormality in fasting blood parameters in all groups was found. Compared to the control group among male participants, the 250 mg OPP group showed an improved serum triglyceride level. There were no statistically significant changes in all blood parameters from day 1 to day 60 with the exception of triglyceride level. Conclusion: The absence of SAEs reported and no abnormal findings in biochemistry and hematology results suggested that the 250 mg OPP was safe to be taken by hyperlipidemic patients with a high probability of reducing triglyceride level in hyperlipidemic male patients The outcomes from this phase II trial suggest that by incorporating OPP supplements into the diet may be a promising strategy for individuals with hyperlipidemia to improve their lipid profiles and reduce cardiovascular risk. However, more research is needed to fully understand the mechanisms of action and establish the long-term efficacy and safety of OPP supplementation in larger scale. Limitation: Small samples size hence lack of diversity (25 subjects per groups) and early sharing of treatment-response results. Clinical Trial Registration:clinicaltrials.gov, identifier NCT04573218.